Students' Perception on Using Cake Application as Learning Vocabulary - Nasution, Agustami; Maryati Salmiah (Institut Agama Islam Negeri Palopo, 2024)
The qualitative study investigated vocabulary knowledge is considered an important tool in language learning. Online learning applications are one technology that can be used to learn languages. Learning among students using applications will increase the use of digital technology in education. Through the internet, students can obtain learning resources. Therefore, this research focuses on using the Cake application as learning vocabulary. data was collected through questionnaires and interviews with students who had used it app for vocabulary improvement. The results show that students find this application useful for learning new vocabulary and very effective. Research reveals that the online Cake application can improve students' language learning experiences and outcomes by increasing students' knowledge. It is said that using the Cake application program can serve as a solution to words understanding problems.